Darkness Administrative Judiciary’s status on Job Exclusion Due to Lack of Educational Qualification - Adel Hamza, Lect. Ruqia (Basra studies journal, 2023)
The Iraqi legislator has set specific conditions that must be met by candidates for public positions upon their appointment. Losing all or part of these conditions allows the appointing authority to terminate the employment relationship by excluding the individual from the job. One of the crucial conditions is having the required educational qualification for the job, as it is essential for effective work in various fields. It is unreasonable for someone without the necessary educational qualifications, capabilities, and experience to occupy a position. In cases where this condition is not met, the administration typically resorts to excluding the employee due to the lack of a hiring condition. We observed that the administration may opt to reappoint based on the minimum certification. Therefore, we deemed it important to study the administrative judiciary’s oversight over the administration’s authority to resort to exclusion when the educational qualification condition is not met.